Thermodynamics-Augmented Reality as a Visual Learning Media to Improve Student Creativity - Hildayanti, Juis; Janati, Janati; Ilqi Qurtubi, Galih (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
In the digital era, integrating technology in education provides a great opportunity to improve the quality of learning. Using smart devices and educational applications creates an interactive learning experience, expands access to global resources, and facilitates collaboration-based learning. In this context, smartphone-based mobile learning (M-learning), especially Android, has become a popular learning medium among teenagers. This technology offers great potential in increasing the effectiveness of the teaching and learning process, especially in materials that require complex visualization, such as thermodynamics in physics. The abstract concept of thermodynamics is often difficult for students to understand without adequate visualization, leading to misconceptions. To overcome this problem, Augmented Reality (AR) technology can be used as a learning medium to combine the real world with digital content in real time, allowing for clearer and more concrete visualizations. The development of AR-based learning media on thermodynamics materials, such as Thermodynamics-Augmented Reality, is expected to reduce misconceptions, increase creativity, and facilitate students' deeper understanding of complex concepts.